The Explanatory Power of the General Theory of Crime: A Comparative Analysis of a General Population and Serious Offender Sample. Issue 5 (3rd May 2016) - Siegfried, Cornelia; Woessner, Gunda
Abstract: The purpose of this study was to investigate—via direct comparison—the fundamental supposition that the general theory of crime should be valid for both criminal and analogous behavior in both an offender and a general population sample. The core constructs of the theory, namely the influence of parenting style on self-control and the relationship with different manifestations of deviance, were analyzed by comparing a sample of incarcerated sexual and violent offenders with a general population sample. The validity of the general theory could only be confirmed for the offender population.